2021
DOI: 10.1017/s0967199420000660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidants on preimplantation embryo developmentin vitro: a review

Abstract: Summary In vitro culture of the embryo is a useful method to treat infertility that shows embryo potential for selecting the best one to transfer and successfully implantation. However, embryo development in vitro is affected by oxidative stresses such as reactive oxygen species that may damage embryo development. Antioxidants are molecules found in fruits, vegetables, and fish that play an important role in reducing oxidative processes. In the natural environment, there is a physiological antioxidant syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 194 publications
0
23
0
Order By: Relevance
“…Various studies have shown that adding antioxidants into embryo culture medium improves in vitro embryo development [ 36 ]. Here, we evaluated the effects of AntiOxBEN2 on embryonic development and quality after supplementation in capacitation medium (CAP) of spermatozoa, fertilization medium (FERT), or both.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown that adding antioxidants into embryo culture medium improves in vitro embryo development [ 36 ]. Here, we evaluated the effects of AntiOxBEN2 on embryonic development and quality after supplementation in capacitation medium (CAP) of spermatozoa, fertilization medium (FERT), or both.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, ROS are considered a double‐edged sword, meaning that a certain amount of them is a prerequisite for the proper functioning of biological phenomena, while high levels of ROS can damage DNA, proteins, and lipids and play an important role in causing pathological events. In the female reproductive system, small amounts of ROS are involved in some biological processes from the maturity of the oocyte to fertilization and embryo development 12 . While high levels of ROS are one of the primary culprits for DNA damage in ovarian granulosa cells and the ovulation process.…”
Section: Discussionmentioning
confidence: 99%
“…One of the least dangerous ways to protect ovaries against chemotherapy is to use antioxidants 5,10 . Using an appropriate dose of antioxidants is noninvasive and can protect cells by reducing oxidative stress and scavenging reactive oxygen species (ROS) 11,12 . High levels of ROS due to increased oxidative stress lead to DNA damage, destruction of the endothelium, and apoptosis of ovarian granulosa cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, supplementation of culture medium with 1 nM of melatonin resulted in optimum oocyte development and nuclear maturation, whereas higher melatonin levels (105 to 107 nM) resulted in detrimental effects on nuclear maturation [197]. Additionally, a recent review highlighted the beneficial effects of AOX supplementation of culture media on the growth improvement of different species of embryos in vitro [198]. To the contrary, no significant effects on embryo development were observed following AOX supplementation of the culture medium [79].…”
Section: Strategies To Minimize Os In Artmentioning
confidence: 99%